Complex adaptive leadership embracing paradox and uncertainty - Obolensky, Nick (Gower, 2014)
Complex Adaptive Leadership, a Gower bestseller, has been taught in corporate leadership programmes, business schools and universities around the world to high acclaim. In this updated paperback edition, the author argues that leadership is a complex dynamic process and should involve all those engaged in a particular enterprise